Dynamic modules of Pinus pseudostrobus and wood panels - Sotomayor-Castellanos, Javier Ramón (2026)
This study compares the physical and dynamic properties of solid Pinus pseudostrobus wood and four types of engineered wood panels: edge-glued, plywood, medium-density fiberboard (MDF), and oriented strand board (OSB). Five groups of specimens were prepared to determine moisture content, density, and dynamic moduli in longitudinal and transverse directions using ultrasound. Moisture contents were relatively homogeneous, with lower variation in industrial panels. In terms of density, MDF and OSB exceeded solid wood, while edge-glued panels showed lower density and greater dispersion. Regarding dynamic moduli, solid wood exhibited the highest longitudinal value, while plywood stood out for its transverse stiffness. Dynamic anisotropy was highest in solid wood, in contrast to the derived panels, with MDF showing an almost isotropic behavior. It is concluded that while solid wood retains advantages in unidirectional applications, plywood, OSB, and MDF offer a combination of dimensional stability, homogeneity, and mechanical competitiveness suitable for bidirectional structural systems and precision furniture. Future lines of research are proposed to optimize anisotropy and the sustainability of these materials.